Understanding media and culture - Lule, Jack; Saylor Foundation; BC Open Textbook Project; BCcampus (Saylor Foundation, 2012)
"This book's title tells its intent. It is written to help you understand media and culture. The media and culture are so much a part of our days that sometimes it is difficult to step back and appreciate and apprehend their great impact on our lives. The book's title, and the book itself, begin with a focus squarely on media. Think of your typical day. If you are like many people, you wake to a digital alarm clock or perhaps your cell phone. Soon after waking, you likely have a routine that involves some media. Some people immediately check the cell phone for text messages. Others will turn on the computer and check Facebook, email, or websites. Some people read the newspaper. Others listen to music on an iPod or CD. Some people will turn on the television and watch a weather channel, cable news, or Sports Center. Heading to work or class, you may chat on a cell phone or listen to music. Your classes likely employ various types of media from course management software to PowerPoint presentations to DVDs to YouTube. You may return home and relax with video games, television, movies, more Facebook, or music. You connect with friends on campus and beyond with text messages or Facebook. And your day may end as you fall asleep to digital music. Media for most of us are entwined with almost every aspect of life and work. Understanding media will not only help you appreciate the role of media in your life but also help you be a more informed citizen, a more savvy consumer, and a more successful worker. Media influence all those aspects of life as well."--BCcampus website.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Description based on version viewed on BCcampus OpenEd website; title from pdf title page.
Keywords: Culture -- Textbooks; Mass media -- Textbooks; Social media -- Textbooks; Electronic books